The relationship between job training and sme corporation performance in Kuantan, Pahang - Nurliyana, Nasir (2016)
Job training is an important element for any organization to maintain their performance to measure their performance is higher and can compete with a big company n success of company. Many important and benefit can be obtained by any organization when the employee can be achieved when implementing a training in work place. This research is carried out to find The Relationship between Job Training and SME Corporation Performance in Kuantan, Pahang. The objective of this research is to identify the job training variables and company performance variables and to find the relationship between job training and company performance. Some of company SMEs located in Kuantan, Pahang was selected as a scope for this study. Participant randomly selected and the manager, assistance manager or supervisor of SMEs company are the respondent to answer the questionnaire in this study. Two instruments were used to collect data which is survey questionnaire which consist of open-ended and closed-ended questions. The participants are 100 randomly selected managers, assistance manager and supervisor from different age, gender, race and so on. The result showed that ability (independent variable) and company performance (dependent variable) is the effects that influence the job training and company performance. The correlation showed that ability and company performance have a strong relationship.